Optimization Design of Sand Washer Based on CFD-DEM Coupling - Zhang, Yi; Wang, Zhen; Zhang, Daqin; Tang, Bangyao (Scientific Journal of Technology, 2026)
Sand washers play a crucial role in the oil drilling field. To improve the drilling cuttings screening efficiency of sand washers, it is necessary to optimize the structure of the sand washer's vibrating screen. This paper takes the vibrating screen of the sand washer as the research object and investigates how its screening performance is affected by multiple factors such as amplitude, frequency, vibration mode, and screen mesh. Firstly, the CFD-DEM method is adopted for numerical simulation to study the influence of the vibration parameters of the sand washer's vibrating screen on the screening efficiency. Secondly, in order to achieve the optimal drilling cuttings screening efficiency, a response surface optimization analysis with the maximum screening efficiency as the optimization objective is established using the simulation results under different parameters, and the optimal combination of various parameter values is determined. Finally, the reliability of the numerical simulation is verified by comparing the results of the sand washer experiment with the numerical simulation results.